1966
DOI: 10.1128/aem.14.4.608-615.1966
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Wines Fermented with Various Malo-lactic Bacteria1

Abstract: PILONE, GORDON J. (University of California, Davis), RALPH E. KUNKEE, AND A. DINSMOOR WEBB. Chemical characterization of wines fermented with various malo-lactic bacteria. Appl. Microbiol. 14:608-615. 1966.-Six malo-lactic strains of lactic acid bacteria were isolated from California wines and identified as Lactobacillus delbrueckii, L. buchneri, L. brevis, Leuconostoc citrovorum, and two strains of Pediococcus cerevisiae. Malo-lactic fermentation was induced in separate lots of wine by inoculation of each lot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

1975
1975
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 1 publication
0
15
0
2
Order By: Relevance
“…Individual samples of wine, grape musts, fresh grapes, ground grape skins, vine leaves, sugarcane and sewage water were enriched in 100 ml modified Rogosa (MR) broth [12] and incubated at 26 °C for 24-48 h. Cultures were then centrifuged (15 300 x g, 10 min) and the supernatants passed through a sterile Millipore filter (0.22 /~m pore size). The filtrate was assayed for the presence of phages by spotting the suspension on double-layer agar plates (MR + 0.15% CaC12 • 2H20 + 0.65% agar, pH 4.5) previously seeded with one of 39 Leuconostoc strains ( Table 1).…”
Section: Isolation Of Bacteriophagesmentioning
confidence: 99%
“…Individual samples of wine, grape musts, fresh grapes, ground grape skins, vine leaves, sugarcane and sewage water were enriched in 100 ml modified Rogosa (MR) broth [12] and incubated at 26 °C for 24-48 h. Cultures were then centrifuged (15 300 x g, 10 min) and the supernatants passed through a sterile Millipore filter (0.22 /~m pore size). The filtrate was assayed for the presence of phages by spotting the suspension on double-layer agar plates (MR + 0.15% CaC12 • 2H20 + 0.65% agar, pH 4.5) previously seeded with one of 39 Leuconostoc strains ( Table 1).…”
Section: Isolation Of Bacteriophagesmentioning
confidence: 99%
“…jensenii and Lact. plantarum (Douglas and Cruess 1936 ;Vaughn 1955 ;Fornachon 1957 ;Du Plessis and van Zyl 1963 ;Pilone et al 1966 ;Chalfan et al 1977 ;Sozzi 1977, 1979 ;Costello et al 1983 ;Lafon-Lafourcade et al 1983 ;Davis et al 1986a, b ;Dicks and van Vuuren 1988 ;Sieiro et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it has been suggested that excess formation of acetic acid, when it occurs, may not come from the bacteria, but rather from the yeast under the stressed conditions resulting from competition between the yeast and the bacteria for nutrients [28]. We have not been able to mimic conditions to bring about formation of acetic acid, other than the small amount normally associated with the malolactic fermentation [29], aor have we been able to substantiate any reports of an increased acetic acid formation from this practice in the California industry. An Australian report [30] supports the use of simultaneous fermentations where sensory evaluation revealed such wines to be free from undesirable odors.…”
Section: Timing Of the Malolactic Fermentationmentioning
confidence: 96%
“…Just as important is the criterion that no offflavors or off-odors are produced by the bacteria during the commercial production of wine. We have previously shown that sensory quality of the resulting wine by 'good' strains of bacteria is affected, but only to a very limited or subtle extent, by that strain [17]. More recent work, with Chardonnay and with red French-American hybrid grapes from the Eastern United States [18,19], has also shown a slight dependence of wine flavor upon the strain of malolactic organism used [20].…”
Section: Characte~tics Of Desirable Strains Of Matolactic Bacteria Fmentioning
confidence: 99%
See 1 more Smart Citation